Kemandirian Keuangan Pemerintah Kota Tangerang Dalam Membiayai Kegiatan Perekonomian - Adi Rizfal Efriadi (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
This research analyzes trends of APBD Kota Tangerang and financial performance of Pemerintah Kota Tangerang. This research used descriptive and qualitative method where 19922008 was observed. 1992-1999 is assumed that the year is before autonomy implementation and the year of 2001-2008 is after autonomy implementation policy. Time of research is December 2010-April 2011. The results showed that financial performance of Pemerintah Kota Tangerang is lower compared before autonomy implementation. The average of it is 1.17%. Differently, the index during autonomy policy raised 0.67%. The result of this research becomes the indication that Pemerintah Kota Tangerang has not yet fully independent in financial management as an effort of economic improvements.